Clinical Spectrum of Uveitis Induced by Herpes Simplex Virus with Posterior Pole Involvement at Initial Presentation: A Case Series and Literature Review. (17th November 2022) - Hu, Feng; She, Haicheng; Cao, Xusheng; Wang, Jiawei; Lin, Caixia; Peng, Xiaoyan
ABSTRACT: Purpose: To report four cases of herpes simplex virus-induced uveitis with posterior pole involvement at initial presentation. Case Presentations: In case 1, the posterior pole initially showed dense vitreous hemorrhage from the optic disc, multiple subretinal lesions around the optic disc, and retinal arterial sheath prior to retinal necrosis. In case 2, the posterior pole presented with optic disc edema, retinal venous tortuosity, and arterial sheathing around the optic disc prior to the peripheral retinal necrosis. In case 3 diagnosed with posterior herpetic uveitis, the posterior pole showed retinal arterial sheath and macular structural abnormities. In case 4, the posterior pole demonstrated optic disc swelling, along with perivascular retinal hemorrhage 4 days prior to peripheral retinal necrosis. Conclusions: Posterior pole involvement might occur either solely or before the development of peripheral retinal necrosis in patients with herpes simplex virus-induced acute retinal necrosis with and without prior central nervous system herpetic virus infection.